2016
DOI: 10.1007/s00253-016-7766-3
|View full text |Cite|
|
Sign up to set email alerts
|

Towards novel Cry toxins with enhanced toxicity/broader: a new chimeric Cry4Ba / Cry1Ac toxin

Abstract: Attempts have been made to express or to merge different Cry proteins in order to enhance toxic effects against various insects. Cry1A proteins of Bacillus thuringiensis form a typical bipyramidal parasporal crystal and their protoxins contain a highly conserved C-terminal region. A chimerical gene, called cry(4Ba-1Ac), formed by a fusion of the N-terminus part of cry4Ba and the C-terminus part of cry1Ac, was constructed. Its transformation to an acrystalliferous B. thuringiensis strain showed that it was expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Furthermore, in Cry1Ac, a deletion of 56 amino acids at the N-terminus, which included helix α-1, increase the toxic activity against Pectinophora gossypiella by 107-fold ( Mandal et al, 2007 ) and against Plutella xylostella and Ostrinia nubilalis by 350-fold ( Tabashnik et al, 2011 ). However, the toxic activity of Cry4Ba against A. aegypti was abolished when more than 38 amino acids were removed from the N-terminus ( Pao-intara et al, 1988 ) and, in the case of chimeric proteins formed by a fusion of N-terminus of Cry4Ba and the C-terminus of Cry1Ac, an increase of toxicity against C. pipiens larvae was observed ( Zghal et al, 2017 ). Although these findings confirm the importance of the N-terminal region in the toxicity of Cry proteins, the N-terminal deletions found in our variants did not affect their toxic activity against A. aegypti or C. quinquefasciatus larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in Cry1Ac, a deletion of 56 amino acids at the N-terminus, which included helix α-1, increase the toxic activity against Pectinophora gossypiella by 107-fold ( Mandal et al, 2007 ) and against Plutella xylostella and Ostrinia nubilalis by 350-fold ( Tabashnik et al, 2011 ). However, the toxic activity of Cry4Ba against A. aegypti was abolished when more than 38 amino acids were removed from the N-terminus ( Pao-intara et al, 1988 ) and, in the case of chimeric proteins formed by a fusion of N-terminus of Cry4Ba and the C-terminus of Cry1Ac, an increase of toxicity against C. pipiens larvae was observed ( Zghal et al, 2017 ). Although these findings confirm the importance of the N-terminal region in the toxicity of Cry proteins, the N-terminal deletions found in our variants did not affect their toxic activity against A. aegypti or C. quinquefasciatus larvae.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, and thanks to the determination of the Cry1Ac1 full-length toxin 3D structure ( [19]; PDB 4W8J), Zghal et al [21] constructed a 116 KDa chimeric toxin called Cry(4Ba-1Ac) by fusing DI-DIV from Cry4Ba to DV-DVII from Cry1Ac1, using PCR amplification and cloning techniques. This represents a unique case in which other domains, apart from Cry toxin toxic domains, have been swapped.…”
Section: Res Res* Res*: Restriction Enzyme Sitementioning
confidence: 99%
“…Although the functions of DIV-DVII are not known, they have been related with crystal formation, toxin stability, and selective solubilization in the insect gut. In addition, it has recently been suggested that Domains V and VII could also be interacting domains with proteins present in gut membranes, and hence be involved in the recognition of receptors of the full toxin [21].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, to circumvent resistance, several novel strategies like gene pyramiding and generation of chimeric toxins ( Zghal et al, 2017 ; Khabbazi et al, 2018 ; Sellami et al, 2018 ; Rathinam et al, 2019 ; Zubair et al, 2019 ; Salim et al, 2020 ); RNAi-mediated knockdown ( Tian et al, 2015 ; Han et al, 2017 ; Luo et al, 2017 ; Ni et al, 2017 ; Shen et al, 2017 ); CRISPR/Cas9 mediated genome editing ( Zhang et al, 2018 ; Bisht et al, 2019 ; Tyagi et al, 2020 ) and multiomic approaches ( Du et al, 2018 ; Peng et al, 2020 ) for the management of insect resistance have also become an integral part of pest management through biotechnology.…”
Section: Introductionmentioning
confidence: 99%